2019
DOI: 10.3390/molecules24183367
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interlaminar Fracture Toughness and Impact Performance of Carbon Fiber/Epoxy Laminated Composite by Using Thermoplastic Fibers

Abstract: The effects of thermoplastic polyimide (PI) and polypropylene (PP) fibers and areal density of toughened layer on interlaminar fracture toughness and impact performance of carbon fiber/epoxy (CF/EP) laminated composites were studied. Mode I interlaminar fracture toughness (GIC) was analyzed via double cantilever beam (DCB) tests. When comparing for the toughener type, PI played a positive role in enhancing the mode-I fracture toughness, while PP was not effective due to the less fiber bridge formed during comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Following Ramirez et al [36], other groups have shown a dependence of IFT on the areal density of the interleaving veil. A linear relationship up to a point between areal density of microfibre interleaves and IFT was reported by Chen et al [109] and Beylergil et al [92,110]. In general, we observe that IFT data from the literature usually show significantly higher increase in mode I and mode II fracture toughness for microfibre interleaves than nanofibre ones.…”
Section: Nanofibre Versus Microfibresupporting
confidence: 85%
“…Following Ramirez et al [36], other groups have shown a dependence of IFT on the areal density of the interleaving veil. A linear relationship up to a point between areal density of microfibre interleaves and IFT was reported by Chen et al [109] and Beylergil et al [92,110]. In general, we observe that IFT data from the literature usually show significantly higher increase in mode I and mode II fracture toughness for microfibre interleaves than nanofibre ones.…”
Section: Nanofibre Versus Microfibresupporting
confidence: 85%
“…Interleaving improved the threshold impact force by 60%, reduced the rate of impact damage growth rate to one-half with impact height, and also reduced the impact damage growth rate from 0.115 to 0.105 mm 2 /N with impact force. Recently, Chen et al 177 measured 92% and 300% increase in maximum load and elastic energy (difference between impact energy and absorbed energy) of CF/EP composites interleaved with polypropylene and polyimide fibers under low-velocity impact.…”
Section: Effects Of Interleaving On Various Properties Of Fiber-reinf...mentioning
confidence: 99%
“…However, the data for the laminates with short Kevlar fibers shows a wider scatter due to the uneven distribution of the Kevlar fibers, which probably comes from the manually spread method. Recently various commercial polymer films have been utilized as interleaving materials in CFRPs, such as chopped aramid fibers [16], polyimide and polypropylene fibers [17], polypropylene nonwoven fabric [18], silk fibers interleave [19] and resulted in varied success in the toughness improvement of the composites. However, the incorporation of commercial interleaf with insulating or soft fibers will lead to the reduction of the electrical conductivity of the laminates and possible decrease in-plane strength and modulus of the laminates [16] due to the high electrical insulation and weak mechanical properties of the polymer material in nature.…”
Section: Introductionmentioning
confidence: 99%